Carl Peters and Africa : a myth in the public opinion, litterature and political propaganda in germany - (:unkn) unknown (My University, 2006)
Carl Peters (1856-1918) is generally known as a young doctor of philosophy who traveled as a simple civilian to Zanzibar where he acquired the territories which later formed the colony of German East Africa. Less known is the fact that the public figure of Peters is made up of three characters , which are quite distinct: firstly, Peters was an actual historical personality, engaged, as he was, in the colonial vicissitudes. Secondly, Peters was an author, who tried to defend the enterprises of his first avatar. And thirdly, Peters became the literary character or rather the various literary characters that he himself and a plethora of other German authors depicted - from the time of Wilhelm II, throughout the Weimar Republic all the way to the end of the Hitler era - in their attempts to use the conquistador of Hanover for the propagation of their various political interests. The present study analyses the transformations that Carl Peters image underwent in German public opinion, literature and political propaganda from 1884 (the beginning of the Berlin West African conference) up to the year 1945, which marks both the end of Nazism and of the dream of a German colonial Empire . The central thesis that emerges from this analysis is that Carl Peters and his life represent a myth that continuously accompanied Germany s colonial ambitions.
Keywords: African Research